PERANAN MASYARAKAT BANJAR KAJENG, DESA PEMOGAN DALAM PENGELOLAAN DAYA TARIK EKOWISATA TAHURA NGURAH RAI, DENPASAR, PROVINSI BALI - Gunarsa, I Nyoman; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
This paper aims to determine the role of Banjar Kajeng community, Pemogan Village and relationship between government, investors and local communities in the management of ecotourism attraction in Tahura Ngurah Rai, Denpasar.Research method that used in this research is qualitative method, with theoretical analysis of typology of a community participation and theory of conflict perspective and equipped by tables of tourism actors involved and the patterns of relationship among tourism actors involved in the management of tourist attraction in Tahura Ngurah Rai. The results obtained by this reasearch are the Banjar Kajeng community participation type is manipulative participation and the relationship between the Government, Investors and Local Communities in the Management of Ecotourism attractions in Tahura Ngurah Rai are at conflict stage.
Keywords: Participation, Ecotourism, Tahura Ngurah Rai.